2011
DOI: 10.4067/s0717-95022011000400018
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la Anatomía en Cadáver y Modelos Anatómicos: Impresión de los Estudiantes

Abstract: RESUMEN: En la enseñanza de la anatomía humana diversos autores señalan que la base del conocimiento del cuerpo humano es el cadáver. Aprender anatomía con el recurso, cadáver, contribuye en gran medida a la comprensión de la forma, ubicación, relaciones, espacio y distancia de los diferentes órganos y estructuras del cuerpo humano.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
1
11
0
3
Order By: Relevance
“…However they did not present as a promising option for the practical assessments of Anatomy, obtaining considerable rejection by the participating students. This result, corroborated by Collipal Larre and Silva Mella's study, 22 the use of these models, for the practical anatomical study, results in an easy, unreal, artificial and invariable teaching. However Falcão et al study, 23 unlike the above study and the results obtained, they observed that construction of similar structures is possible for cadaveric.…”
Section: Discussionsupporting
confidence: 69%
“…However they did not present as a promising option for the practical assessments of Anatomy, obtaining considerable rejection by the participating students. This result, corroborated by Collipal Larre and Silva Mella's study, 22 the use of these models, for the practical anatomical study, results in an easy, unreal, artificial and invariable teaching. However Falcão et al study, 23 unlike the above study and the results obtained, they observed that construction of similar structures is possible for cadaveric.…”
Section: Discussionsupporting
confidence: 69%
“…É notável a necessidade de encontrar caminhos que permitam melhorar a qualidade da aprendizagem nesta disciplina que, muitas vezes, se caracteriza por apresentar índices elevados de reprovação (MONTES et al, 2005), Grande parte de sua carga horária são de aulas práticas, uma forma eficaz de oferecer contato do futuro profissional direto com a realidade. Acadêmicos e profissionais acreditam que a Anatomia Humana deve ser um assunto essencialmente prático, onde não só a dissecação ocupe posição de destaque, mas também técnicas de imagem e resolução de problemas clínicos (COLLIPAL, 2011). Acadêmicos bem-sucedidos aprendem mais usando tanto a memorização superficial como o profundo entendimento e a visualização.…”
Section: Introductionunclassified
“…According to Collipal and Silva (2011), students learn more when the practical ways of learning are varied. Thus, the most interesting would be the use of human corpses and artificial anatomical models simultaneously (Collipal & Silva, 2011).…”
Section: Acta Scientiarum Biological Sciencesmentioning
confidence: 99%
“…Thus, the most interesting would be the use of human corpses and artificial anatomical models simultaneously (Collipal & Silva, 2011). …”
Section: Acta Scientiarum Biological Sciencesmentioning
confidence: 99%